Behavioral Health's Integration Within a Care Network and Health Care Utilization. (30th May 2018) - McClellan, Chandler; Flottemesch, Thomas J.; Ali, Mir M.; Jones, Jenna; Mutter, Ryan; Hohlbauch, Andriana; Whalen, Daniel; Nordstrom, Nils
Abstract : Objective: Examine how behavioral health (BH) integration affects health care costs, emergency department (ED) visits, and inpatient admissions. Data Sources/Study Setting: Truven Health MarketScan Research Databases. Study Design: Social network analysis identified "care communities" (providers sharing a high number of patients) and measured BH integration in terms of how connected, or central, BH providers were to other providers in their community. Multivariable generalized linear models adjusting for age, sex, number of prescriptions, and Charlson comorbidity score were used to estimate the relationship between the centrality of BH providers and health care utilization of BH patients. Data Collection/Extraction Methods: Used outpatient, inpatient, and pharmacy claims data from six Medicaid plans from 2011 to 2013 to identify study outcomes, comorbidities, providers, and health care encounters. Principal Findings: Behavioral health centrality ranged from 0 (no BH providers) to 0.49. Relative to communities at the median BH centrality (0.06), in 2012, BH patients in communities at the 75th percentile of BH centrality (0.31) had 0.2 fewer admissions, 2.1 fewer all‐cause ED visits, and accrued 1, 947 fewer costs, on average. Conclusions: Increased behavioral centrality was significantly associated with a reduced number of ED visits, less frequent inpatient admissions, and lower overall health care costs.